Analysis of the Impact of Tourism Development on Economic and Socio-Cultural Aspects of Society (Case Study at Bukit Jaddih Tourism Village, Socah District, Bangkalan Regency) - Muhammad Iqbal Maulana; Abdur Rohman (Managing: Jurnal Bisnis dan Manajemen, 2024)
Bukit Jaddih Village, Socah District, Bangkalan Regency, is intensively carrying out tourism development. Development in every process will have impacts, therefore there is a need for research on these impacts in order to avoid, reduce negative impacts and encourage positive impacts. This research process uses descriptive research methods using a qualitative approach. The focus of this research is the implementation of tourism industry development which includes the development of tourist objects and attractions, infrastructure, tourism marketing and promotion, as well as human resource development. The next focus is the impact on the economic and socio-cultural conditions of the community due to tourism development and previous conditions. The results of this research are a positive impact on tourism in Bukit Jaddih village in economic and social aspects, namely the opening of new job opportunities, reduced unemployment rates and the development of existing local arts and culture.